Fresh-keeping packaging bag as well as preparation method and application thereof
By using Fe3O4 to modify the silver-loaded zirconium phosphate and modified MOF materials in the fresh-keeping packaging bag, and applying magnetic field induction, the problem of high water vapor transmission rate of PLA and PBAT material packaging bags is solved, achieving better fruit and vegetable freshness and packaging performance.
Patent Information
- Application Number
- CN202510266142.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The existing PLA and PBAT fresh-keeping packaging bags have high water vapor transmittance, resulting in excessive water loss in fruits and vegetables during the fresh-keeping process, affecting the fresh-keeping effect.
Fe3O4 modified silver-loaded zirconium phosphate and modified MOF materials were mixed with PLA and PBAT, and fresh-keeping packaging bags were prepared by melt extrusion blown film, and a magnetic field was applied during the preparation process to induce the Fe3O4 modified silver-loaded zirconium phosphate.
It significantly reduces the water vapor transmission rate of fresh-keeping packaging bags, slows down the water loss of fruits and vegetables, improves the fresh-keeping effect, and enhances the mechanical properties and antibacterial properties of the packaging bags.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging bags, and in particular relates to a fresh-keeping packaging bag and a preparation method and application thereof. Background Art
[0002] At present, the main preservation technologies for fruits and vegetables include low-temperature storage, fresh-keeping bag (film) packaging, 1-MCP treatment, controlled atmosphere storage, etc. Among them, fresh-keeping packaging bags are the most commonly used. Fresh-keeping packaging bags regulate the content of O2, CO2 and H20 in the environment around fruits and vegetables, inhibit the respiration of fruits and vegetables, delay the aging of fruits and vegetables, and achieve the purpose of extending the shelf life.
[0003] Polyethylene (PE) is currently the most commonly used raw material for fresh-keeping packaging bags. It has a high water vapor barrier effect, but it is difficult to degrade. Its large-scale use poses a huge threat to water and soil resources. Polylactic acid (PLA) is a green and environmentally friendly biodegradable polymer material with excellent mechanical properties, air permeability and carbon dioxide permeability. Polybutylene adipate / terephthalate (PBAT) is a thermoplastic biodegradable plastic with excellent ductility, impact resistance and film-forming properties. It is an excellent material for toughening PLA. However, the water vapor permeability of biodegradable materials such as PLA and PBAT is much greater than that of traditional PE. Therefore, when used for fruit and vegetable preservation, it will lose more water than PE preservation materials, resulting in a decrease in color and fullness, or even corruption. Summary of the invention
[0004] The object of the present invention is to provide a fresh-keeping packaging bag and a preparation method and application thereof, so as to solve the problem of high water vapor permeability of existing fresh-keeping packaging bags made of PLA and PBAT.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A fresh-keeping packaging bag comprises the following raw materials in parts by weight: PLA 70-90 parts; PBAT 10-30 parts; Fe3O4 modified silver-supported zirconium phosphate 0.5-2 servings; 15-20 parts of modified MOF material; Chain extender 0.5-2 parts; Antioxidant 0.2-0.8 parts; Lubricant 0.2-0.6 parts.
[0006] As a preferred technical solution of the present invention, the Fe3O4 modified silver-loaded zirconium phosphate is prepared by the following steps: The silver-loaded zirconium phosphate was mixed with deionized water and heated to 60°C, and a mixed aqueous solution of ferric chloride hexahydrate and ferrous chloride tetrahydrate was added. After stirring evenly, ammonia water was added to adjust the pH value to 12, and the mixture was reacted at 80°C for 0.5-1h. The mixture was filtered, and the filter cake was washed and dried to obtain Fe3O4-modified silver-loaded zirconium phosphate.
[0007] As a preferred technical solution of the present invention, the usage ratio of silver-loaded zirconium phosphate, ferric chloride hexahydrate and ferrous chloride tetrahydrate in the above process is 30:1.16-3.48:1.7-5.1.
[0008] When preparing Fe3O4-modified silver-loaded zirconium phosphate, the mass ratio of the silver-loaded zirconium phosphate and the iron salt is limited to an appropriate range. If the amount of the iron salt is too low, the magnetic properties of the Fe3O4-modified silver-loaded zirconium phosphate will be low, making it difficult to arrange the silver-loaded zirconium phosphate in a magnetic field, thereby failing to achieve a better gain purpose. If the amount of the iron salt is too high, the silver-loaded zirconium phosphate will be over-coated, thereby reducing the contact area between the silver-loaded zirconium phosphate and the bacteria, resulting in a poor antibacterial effect.
[0009] As a preferred technical solution of the present invention, the mass fraction of the ammonia water is 25-28%.
[0010] As a preferred technical solution of the present invention, the silver-loaded zirconium phosphate is silver-loaded zirconium phosphate HTB-032, with an average particle size of 1.6um, which is a broad-spectrum antibacterial agent with lasting bactericidal and antibacterial effects, harmless to the human body, non-irritating to the skin, and a safe and non-toxic product.
[0011] As a preferred technical solution of the present invention, the modified MOF material is prepared by the following steps: The MOF material is added to an ethanol solution, dispersed evenly by ultrasonication, epoxy polyethylene glycol silane is added, reacted at 15-75° C. with stirring for 6-8 hours, filtered, and the filter cake is washed and dried to obtain a modified MOF material.
[0012] As a preferred technical solution of the present invention, in the above process, the mass ratio of MOF material to epoxy polyethylene glycol silane is 10:0.5-2, and the amount of ethanol solution used is 8-15 times the mass of the MOF material.
[0013] When preparing the modified MOF material, the present invention limits the mass ratio of the MOF material and the epoxy polyethylene glycol silane to an appropriate range. If the amount of epoxy polyethylene glycol is too low, the improvement effect on the dispersibility of the MOF material in the matrix is not obvious, and it is difficult to fully exert the reinforcement and other effects. If the amount of epoxy polyethylene glycol is too high, the pore structure in the MOF material will be blocked, the moisture absorption effect of the MOF material on water vapor will be reduced, and the water vapor permeability of the fresh-keeping packaging bag will be affected.
[0014] As a preferred technical solution of the present invention, the mass fraction of the ethanol solution is 60-95%.
[0015] As a preferred technical solution of the present invention, the MOF material is MIL-101 (Cr) and / or MOF-303. Both MIL-101 (Cr) and MOF-303 are metal organic framework materials with rich internal pores and good hygroscopicity.
[0016] As a preferred technical solution of the present invention, the molecular weight of the epoxy polyethylene glycol silane (Silane-PEG-EPO) is 0.4-10K.
[0017] As a preferred technical solution of the present invention, the chain extender is one or both of a dioxazoline chain extender and an isocyanate chain extender with a functionality greater than 2.
[0018] As a preferred technical solution of the present invention, the bisoxazoline chain extender is at least one selected from 2,2-bis(2-oxazoline), 2,2'-(1,3-phenylene)-bisoxazoline and 2,2'-(1,4-phenylene)-bisoxazoline.
[0019] As a preferred technical solution of the present invention, the isocyanate chain extender is selected from at least one of hexamethylene diisocyanate, toluene diisocyanate and diphenylmethane diisocyanate.
[0020] As a preferred technical solution of the present invention, the antioxidant is at least one selected from antioxidant 1010, antioxidant 168 and antioxidant 264.
[0021] As a preferred technical solution of the present invention, the lubricant is at least one of zinc stearate, N,N'-ethylene bisstearamide and polyethylene wax.
[0022] The method for preparing the fresh-keeping packaging bag comprises the following steps: S1, PLA and PBAT were dried at 60°C for 10 h, and then added into a mixer together with Fe3O4-modified silver-loaded zirconium phosphate, modified MOF material, chain extender, antioxidant and lubricant, mixed evenly and then added into a twin-screw extruder, melt blended, water-cooled and pelletized to obtain pellets; S2, adding the pellets into a single screw film blowing machine for extrusion and film blowing to obtain a fresh-keeping film; S3, placing the cling film in an environment at 60-80°C, then applying a magnetic field with a magnetic field strength of 0.1-0.5T perpendicular to the cling film, and heat-treating for 6-12 hours, then removing the magnetic field, cutting and bagging the obtained cling film, and obtaining a fresh-keeping packaging bag.
[0023] As a preferred technical solution of the present invention, the temperatures of the twin-screw extruder are 135°C, 150°C, 160°C, 170°C, 165°C, 160°C, and 150°C, respectively, and the screw speed is 100r / min.
[0024] As a preferred technical solution of the present invention, the temperatures of the heating sections of the film blowing machine from the feed port to the die are 130°C, 160°C, 165°C, and 140°C respectively, and the screw speed is 30r / min.
[0025] The application of the above-mentioned fresh-keeping packaging bag in preserving fruits and vegetables.
[0026] Beneficial effects of the present invention: 1. The present invention provides a fresh-keeping packaging bag, which adopts Fe3O4-modified silver-loaded zirconium phosphate and modified MOF material as fillers, is mixed with PLA and PBAT, and is matched with conventional additives to be obtained by melt extrusion and blown film. The fresh-keeping packaging bag has good biodegradability, is environmentally friendly and healthy, and has good barrier properties, mechanical properties and antibacterial properties, and has a good fresh-keeping effect on fruits and vegetables.
[0027] 2. The present invention modifies the surface of flaky silver-loaded zirconium phosphate with ferrosoferric oxide, and performs magnetic field induction during the preparation of the fresh-keeping film, so that the Fe3O4-modified silver-loaded zirconium phosphate is directional and regularly arranged in the film, reducing the agglomeration problem of the Fe3O4-modified silver-loaded zirconium phosphate, so that the antibacterial and reinforcing effects of the silver-loaded zirconium phosphate can be fully exerted. In addition, the uniformly distributed Fe3O4-modified silver-loaded zirconium phosphate forms an inorganic barrier layer in the film, combined with the strong hygroscopicity of Fe3O4 itself, and ultimately greatly reduces the water vapor permeability of the fresh-keeping packaging bag through the barrier effect and hygroscopic effect, effectively solving the problem of high water vapor permeability of the existing fresh-keeping packaging bags made of PLA and PBAT materials.
[0028] 3. The present invention uses epoxy polyethylene glycol silane to modify the highly hygroscopic MOF material. On the one hand, the dispersibility of the MOF material in the matrix is improved, so that the MOF material can fully exert its hygroscopic effect and further reduce the water vapor permeability of the fresh-keeping packaging bag. On the other hand, the active epoxy groups in the epoxy polyethylene glycol silane react with the hydroxyl and carboxyl groups of PLA and PBAT to improve the compatibility between PLA and PBAT, enhance the bonding strength between the interfaces, and achieve the improvement of mechanical properties. In addition, the flexible polyethylene glycol chain carried by the epoxy polyethylene glycol silane also has a gain effect on the mechanical properties of the fresh-keeping packaging bag. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0030] The silver-loaded zirconium phosphate in the present application is silver-loaded zirconium phosphate HTB-032, with an average particle size of 1.6um, PLA brand Lx-175, a melt index of 6.2g / 10min (210℃ / 2.16kg), and a density of 1.25g / cm 3 The PBAT grade is TH-801T, the melt index is 3.4g / 10min (190℃ / 2.16kg), and the density is 1.24g / cm 3 .
[0031] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.
[0032] Preparation Example 1 Preparation of Fe3O4-modified silver-loaded zirconium phosphate, the steps are as follows: Mix 30 g of silver-loaded zirconium phosphate with 300 mL of deionized water and heat to 60°C, add a mixed solution consisting of 1.16 g of ferric chloride hexahydrate, 1.7 g of ferrous chloride tetrahydrate and 50 mL of deionized water, stir evenly, add 25 wt % ammonia water to adjust the pH value to 12, react at 80°C for 0.5 h, filter, wash and dry the filter cake to obtain Fe3O4 modified silver-loaded zirconium phosphate.
[0033] Preparation Example 2 Preparation of Fe3O4-modified silver-loaded zirconium phosphate, the steps are as follows: Mix 30 g of silver-loaded zirconium phosphate with 300 mL of deionized water and heat to 60°C, add a mixed solution consisting of 2.32 g of ferric chloride hexahydrate, 3.4 g of ferrous chloride tetrahydrate and 100 mL of deionized water, stir evenly, add 28 wt % ammonia water to adjust the pH value to 12, react at 80°C for 1 h, filter, wash and dry the filter cake to obtain Fe3O4 modified silver-loaded zirconium phosphate.
[0034] Preparation Example 3 Preparation of Fe3O4-modified silver-loaded zirconium phosphate, the steps are as follows: Mix 30 g of silver-loaded zirconium phosphate with 300 mL of deionized water and heat to 60°C, add a mixed solution consisting of 3.48 g of ferric chloride hexahydrate, 5.1 g of ferrous chloride tetrahydrate and 100 mL of deionized water, stir evenly, add 28 wt % ammonia water to adjust the pH value to 12, react at 80°C for 1 h, filter, wash and dry the filter cake to obtain Fe3O4 modified silver-loaded zirconium phosphate.
[0035] Comparative Example 1 The preparation of Fe3O4 modified silver-loaded zirconium phosphate is different from that in Preparation Example 1, except that the amount of ferric chloride hexahydrate is adjusted from "1.16g" to "0.58g", and the amount of ferrous chloride tetrahydrate is adjusted from "1.7g" to "0.85g".
[0036] Comparative Example 2 The preparation of Fe3O4 modified silver-loaded zirconium phosphate is different from that in Preparation Example 3, except that the amount of ferric chloride hexahydrate is adjusted from "3.48g" to "4.64g", and the amount of ferrous chloride tetrahydrate is adjusted from "5.1g" to "6.8g".
[0037] Comparative Example 3 This comparative example is silver-loaded zirconium phosphate.
[0038] Preparation Example 4 The preparation steps of modified MOF materials are as follows: 10 g of MIL-101 (Cr) was added to 80 mL of 60 wt% ethanol solution, and ultrasonic dispersion was performed uniformly. 0.5 g of epoxy polyethylene glycol silane was added, and the reaction was stirred at 15° C. for 6 h. The filter cake was filtered, washed and dried to obtain a modified MOF material. The molecular weight of the epoxy polyethylene glycol silane was 0.4K.
[0039] Preparation Example 5 The preparation steps of modified MOF materials are as follows: 10 g of MIL-101 (Cr) was added to 120 mL of 85 wt% ethanol solution, and ultrasonic dispersion was performed uniformly. 1 g of epoxy polyethylene glycol silane was added, and the reaction was stirred at 65° C. for 7 h. The filter cake was filtered, washed and dried to obtain a modified MOF material, wherein the epoxy polyethylene glycol silane had a molecular weight of 5K.
[0040] Preparation Example 6 The preparation steps of modified MOF materials are as follows: 10 g of MIL-101 (Cr) was added to 150 mL of 95 wt% ethanol solution, and ultrasonic dispersion was performed uniformly. 2 g of epoxy polyethylene glycol silane was added, and the mixture was stirred and reacted at 75° C. for 8 h. The mixture was filtered, and the filter cake was washed and dried to obtain a modified MOF material. The molecular weight of the epoxy polyethylene glycol silane was 10K.
[0041] Preparation Example 7 The preparation of the modified MOF material is different from that of Preparation Example 4 only in that an equal mass of MIL-101(Cr) is replaced by an equal mass of MOF-303.
[0042] Comparative Example 4 The preparation of the modified MOF material is different from that of Preparation Example 4 only in that the amount of epoxy polyethylene glycol silane is adjusted from "0.5g" to "0.3g".
[0043] Comparative Example 5 The preparation of the modified MOF material is different from that of Preparation Example 6, except that the amount of epoxy polyethylene glycol silane is adjusted from "2g" to "2.2g".
[0044] Comparative Example 6 The preparation of the modified MOF material is different from that of Preparation Example 4 only in that an equal mass of 3-(2,3-epoxypropoxy)propyltrimethoxysilane is used to replace an equal mass of epoxypolyethylene glycol silane.
[0045] Example 1 A fresh-keeping packaging bag comprises the following raw materials in parts by weight: PLA 70 parts; PBAT 30 copies; Preparation Example 1: Fe3O4-modified silver-loaded zirconium phosphate 0.5 part; 15 parts of the modified MOF material of Preparation Example 4; 0.5 parts of chain extender; Antioxidant 1010 0.2 parts; 0.2 parts of zinc stearate.
[0046] The chain extender is composed of 2,2-bis(2-oxazoline) and hexamethylene diisocyanate in a mass ratio of 1:1.
[0047] The method for preparing the fresh-keeping packaging bag comprises the following steps: S1, PLA and PBAT were dried at 60°C for 10 h, and then added into a mixer together with Fe3O4-modified silver-loaded zirconium phosphate, modified MOF material, chain extender, antioxidant and lubricant, mixed evenly and then added into a twin-screw extruder, melt blended, water-cooled and pelletized to obtain pellets; S2, adding the pellets into a single-screw film blowing machine for extrusion and film blowing to obtain a fresh-keeping film with a thickness of 40 μm; S3, placing the cling film in an environment at 60°C, then applying a magnetic field with a magnetic field strength of 0.1T perpendicular to the cling film, keeping the temperature for 6 hours, removing the magnetic field, cutting and bagging the obtained cling film, and obtaining a fresh-keeping packaging bag.
[0048] The temperatures of the twin-screw extruder are 135° C., 150° C., 160° C., 170° C., 165° C., 160° C., and 150° C., respectively, and the screw speed is 100 r / min.
[0049] The temperatures of the heating sections of the film blowing machine from the feed port to the die are 130° C., 160° C., 165° C., and 140° C., respectively, and the screw speed is 30 r / min.
[0050] Example 2 A fresh-keeping packaging bag comprises the following raw materials in parts by weight: PLA 80 parts; PBAT 20 copies; Preparation Example 1: Fe3O4-modified silver-loaded zirconium phosphate 1 serving; 18 parts of the modified MOF material of Preparation Example 4; 1 part of chain extender; Antioxidant 1010 0.6 parts; 0.4 parts of zinc stearate.
[0051] The chain extender is composed of 2,2-bis(2-oxazoline) and hexamethylene diisocyanate in a mass ratio of 1:1.
[0052] The method for preparing the fresh-keeping packaging bag comprises the following steps: S1, PLA and PBAT were dried at 60°C for 10 h, and then added into a mixer together with Fe3O4-modified silver-loaded zirconium phosphate, modified MOF material, chain extender, antioxidant and lubricant, mixed evenly and then added into a twin-screw extruder, melt blended, water-cooled and pelletized to obtain pellets; S2, adding the pellets into a single-screw film blowing machine for extrusion and film blowing to obtain a fresh-keeping film with a thickness of 40 μm; S3, placing the cling film in an environment at 70°C, then applying a magnetic field with a magnetic field strength of 0.3T perpendicular to the cling film, and heat-treating for 8 hours, then removing the magnetic field, cutting and bagging the obtained cling film, and obtaining a fresh-keeping packaging bag.
[0053] The temperature settings of the twin-screw extruder and the film blowing machine are the same as those in Preparation Example 1.
[0054] Example 3 A fresh-keeping packaging bag comprises the following raw materials in parts by weight: PLA 90 parts; PBAT 10 copies; Preparation Example 1: Fe3O4-modified silver-loaded zirconium phosphate 2 servings; 20 parts of the modified MOF material of Preparation Example 4; 2 parts of chain extender; Antioxidant 1010 0.8 parts; 0.6 parts of zinc stearate.
[0055] The chain extender is composed of 2,2-bis(2-oxazoline) and hexamethylene diisocyanate in a mass ratio of 1:1.
[0056] The method for preparing the fresh-keeping packaging bag comprises the following steps: S1, PLA and PBAT were dried at 60°C for 10 h, and then added into a mixer together with Fe3O4-modified silver-loaded zirconium phosphate, modified MOF material, chain extender, antioxidant and lubricant, mixed evenly and then added into a twin-screw extruder, melt blended, water-cooled and pelletized to obtain pellets; S2, adding the pellets into a single screw film blowing machine for extrusion and film blowing to obtain a fresh-keeping film with a thickness of 40 μm; S3, placing the cling film in an environment at 80°C, then applying a magnetic field with a magnetic field strength of 0.5T perpendicular to the cling film, and heat-treating for 12 hours, then removing the magnetic field, cutting and bagging the obtained cling film, and obtaining a fresh-keeping packaging bag.
[0057] The temperature settings of the twin-screw extruder and the film blowing machine are the same as those in Preparation Example 1.
[0058] Example 4 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the Fe3O4 modified silver-loaded zirconium phosphate in Example 1 is replaced by the product prepared in Preparation Example 2.
[0059] Example 5 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the Fe3O4 modified silver-loaded zirconium phosphate in Example 1 is replaced by the product prepared in Preparation Example 3.
[0060] Example 6 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the modified MOF material in Example 1 is replaced by the product prepared in Preparation Example 5.
[0061] Example 7 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the modified MOF material in Example 1 is replaced by the product prepared in Preparation Example 6.
[0062] Example 8 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the modified MOF material in Example 1 is replaced by the product prepared in Preparation Example 7.
[0063] Comparative Example 1 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the Fe3O4 modified silver-loaded zirconium phosphate in Example 1 is replaced by the product prepared in Control Example 1.
[0064] Comparative Example 2 A fresh-keeping packaging bag, compared with Example 5, the only difference is that the Fe3O4 modified silver-loaded zirconium phosphate in Example 5 is replaced by the product prepared in Control Example 2.
[0065] Comparative Example 3 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the Fe3O4 modified silver-loaded zirconium phosphate in Example 1 is replaced by the substance in Control Example 3.
[0066] Comparative Example 4 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the modified MOF material in Example 1 is replaced by the product prepared in Control Example 4.
[0067] Comparative Example 5 A fresh-keeping packaging bag, compared with Example 7, the only difference is that the modified MOF material in Example 7 is replaced by the product prepared in Control Example 5.
[0068] Comparative Example 6 A fresh-keeping packaging bag, compared with Example 1, the only difference is that the modified MOF material in Example 1 is replaced by the product prepared in Control Example 6.
[0069] Comparative Example 7 A fresh-keeping packaging bag. Compared with Example 1, the preparation method of the fresh-keeping packaging bag is different. No magnetic field treatment is performed, and the fresh-keeping film obtained in step S2 is directly cut and bagged to obtain the fresh-keeping packaging bag.
[0070] The cling film obtained from Example 1 to Example 8 and Comparative Example 1 to Comparative Example 7 was tested, and the test process was as follows: Water vapor permeability test: According to the national standard GB / T1037-1988, the water vapor permeability of each group of cling film was tested using the W3 / 031 water vapor permeability tester produced by Languang Electromechanical Technology Co., Ltd. The test temperature was 38°C and the humidity was 90%RH. Three parallel samples were tested in each group. The water vapor permeability coefficient was calculated by formula (1): WVP=(△m×d) / (A×t×△p) (1) Where: WVP is the water vapor transmission coefficient, unit is g·cm / (cm 2 •s·Pa); △m is the mass added during the test time, in g; d is the sample thickness, in cm; A is the test area, in cm 2 , t is the test time, in h; △p is the steam pressure difference on both sides of the sample, in Pa; Mechanical properties: The specimens were placed in a commercially available CMT4204 10000-capacity mechanical testing machine and subjected to tensile performance tests according to the national standard GB / T1040-2003. The tensile speed was 250 mm / min, and 5 parallel specimens were tested for each group of samples. Antibacterial performance: The antibacterial performance of the film was tested by plate colony counting method. Escherichia coli and Staphylococcus aureus were used as test bacteria. Each group of plastic wrap was cut into squares with a side length of 50 mm. At the same time, the non-antibacterial PE film was cut into squares with a side length of 40 mm as the covering film. 0.2 mL (about 10 5 cfu / mL) of bacterial solution, and drip it onto the test piece in each plate. Cover the bacterial solution with a covering film and culture it in a constant temperature incubator for 24 hours at 37°C and 90% relative humidity. After 24 hours, elute the bacterial solution with eluent and count the eluent using the plate counting method. Test 3 parallel samples for each group of samples and take the average value of the results. Fresh-keeping performance: Buy fresh cherries as samples, put equal amounts of cherries into fresh-keeping packaging bags prepared with fresh-keeping films of each group, seal them and store them in a refrigerator at 4°C. Take them out after 11 days to calculate the good fruit rate and evaluate the fresh-keeping effect. The results are shown in Table 1:
[0071] Analysis of the data in Table 1 shows that the water vapor permeability of the cling film obtained in Examples 1-8 is 2.07-2.23×10 -14 g·cm / (cm 2 •s·Pa), tensile strength is 37.4-43.2MPa, elongation at break is 536-674%, Escherichia coli antibacterial rate is ≥99.1%, Staphylococcus aureus antibacterial rate is ≥98.2%, and the cherry good fruit rate after 11 days of preservation is 95.4-96.8%, which shows that the fresh-keeping film and fresh-keeping packaging bag prepared by the present invention have low water vapor permeability, can slow down the loss of water in fruits and vegetables, have good fresh-keeping effect, and also have good mechanical properties and antibacterial properties.
[0072] More specifically, it can be seen from the test results in Example 1 and Comparative Example 1, and Example 5 and Comparative Example 2 that, when preparing Fe3O4-modified silver-loaded zirconium phosphate, the mass ratio of silver-loaded zirconium phosphate and iron salt is limited to an appropriate range, which is more conducive to obtaining a cling film with good comprehensive performance; it can be seen from the test results in Example 1 and Comparative Example 3 that modifying the surface of flaky silver-loaded zirconium phosphate with ferrosoferric oxide can significantly reduce the water vapor permeability of the cling film and improve the mechanical properties of the cling film; it can be seen from the test results in Example 1 and Comparative Example 4, and Example 7 and Comparative Example 5 that, in When preparing the modified MOF material, limiting the mass ratio of the MOF material and the epoxy polyethylene glycol silane within an appropriate range can significantly reduce the water vapor permeability of the cling film. It can be seen from the test results in Example 1 and Comparative Example 6 that by replacing an equal amount of epoxy polyethylene glycol silane with 3-(2,3-epoxypropoxy)propyltrimethoxysilane, the elongation at break of the cling film finally obtained is significantly reduced. It can be seen from the test results of Example 1 and Comparative Example 7 that if no magnetic field induction treatment is performed during the preparation of the cling film, the water vapor permeability and mechanical properties of the obtained cling film are significantly deteriorated.
[0073] In summary, the present invention adopts Fe3O4-modified silver-loaded zirconium phosphate and modified MOF materials as fillers, mixes with PLA and PBAT, and cooperates with conventional additives to obtain a fresh-keeping packaging bag through melt extrusion and film blowing. The fresh-keeping packaging bag has good biodegradability, is environmentally friendly and healthy, and has good barrier properties, mechanical properties and antibacterial properties, and has a good fresh-keeping effect on fruits and vegetables.
[0074] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A fresh-keeping packaging bag, characterized in that: It includes the following raw materials in parts by weight: PLA 70-90 parts; PBAT 10-30 parts; Fe3O4 modified silver-supported zirconium phosphate 0.5-2 servings; 15-20 parts of modified MOF material; Chain extender 0.5-2 parts; Antioxidant 0.2-0.8 parts; Lubricant 0.2-0.6 parts; The modified MOF material is prepared by the following steps: The MOF material is added to an ethanol solution, dispersed uniformly by ultrasonication, epoxy polyethylene glycol silane is added, stirred and reacted at 15-75° C. for 6-8 hours, filtered, and the filter cake is washed and dried to obtain a modified MOF material; The MOF material is MIL-101 (Cr) and / or MOF-303.
2. A fresh-keeping packaging bag according to claim 1, characterized in that: The Fe3O4 modified silver-loaded zirconium phosphate is prepared by the following steps: The silver-loaded zirconium phosphate was mixed with deionized water and heated to 60°C, and a mixed aqueous solution of ferric chloride hexahydrate and ferrous chloride tetrahydrate was added. After stirring evenly, ammonia water was added to adjust the pH value to 12, and the mixture was reacted at 80°C for 0.5-1h. The mixture was filtered, and the filter cake was washed and dried to obtain Fe3O4-modified silver-loaded zirconium phosphate.
3. A fresh-keeping packaging bag according to claim 2, characterized in that: The dosage ratio of silver-loaded zirconium phosphate, ferric chloride hexahydrate and ferrous chloride tetrahydrate is 30:1.16-3.48:1.7-5.
1.
4. A fresh-keeping packaging bag according to claim 1, characterized in that: The mass ratio of MOF material to epoxy polyethylene glycol silane is 10:0.5-2.
5. A fresh-keeping packaging bag according to claim 1, characterized in that: The molecular weight of the epoxy polyethylene glycol silane is 0.4-10K.
6. A method for preparing a fresh-keeping packaging bag, characterized in that: The method for preparing the fresh-keeping packaging bag according to any one of claims 1 to 5 comprises the following steps: S1, PLA and PBAT were dried at 60°C for 10 h, and then added into a mixer together with Fe3O4-modified silver-loaded zirconium phosphate, modified MOF material, chain extender, antioxidant and lubricant, mixed evenly and then added into a twin-screw extruder, melt blended, water-cooled and pelletized to obtain pellets; S2, adding the pellets into a single screw film blowing machine for extrusion and film blowing to obtain a fresh-keeping film; S3, placing the cling film in an environment of 60-80°C, then applying a magnetic field perpendicular to the cling film, and heat-treating for 6-12 hours, then removing the magnetic field, cutting and bagging the obtained cling film, and obtaining a fresh-keeping packaging bag.
7. The method for preparing a fresh-keeping packaging bag according to claim 6, characterized in that: The magnetic field strength is 0.1-0.5T.
8. Use of a fresh-keeping packaging bag as claimed in any one of claims 1 to 6 in preserving fruits and vegetables.
Citation Information
Patent Citations
High-toughness plastic packaging bag
CN104804345A
Preparation method of novel degradable bio-based fresh-keeping logistics packaging material
CN106751627A
MOFs / PEG cross-linked composite film as well as preparation method and application thereof
CN114632502A
Biodegradable antibacterial composite food packaging film and preparation method thereof
CN118165484A
PLA active air adjusting type fruit and vegetable fresh-keeping bag
CN118909266A
Cited By
Humidity-control preservative film for fruits and vegetables and preparation method of humidity-control preservative film
CN121375244A
A moisture control preservative film for fruits and vegetables and a method for preparing the same
CN121375244B